The Management of Intracranial Aneurysms: Current Trends and Future Directions - Aviraj S. Deshmukh; Stefano M. Priola; Aris H. Katsanos; Gianluca Scalia; Aderaldo Costa Alves; Abhilekh Srivastava; Christine Hawkes (MDPI AG, 2024)
Intracranial aneurysms represent a major global health burden. Rupture of an intracranial aneurysm is a catastrophic event. Without access to treatment, the fatality rate is 50% in the first 30 days. Over the last three decades, treatment approaches for intracranial aneurysms have changed dramatically. There have been improvements in the medical management of aneurysmal subarachnoid haemorrhage, and there has been an evolution of treatment strategies. Endovascular therapy is now the mainstay of the treatment of ruptured intracranial aneurysms based on robust randomised controlled trial data. There is now an expansion of treatment indications for unruptured intracranial aneurysms to prevent rupture with both microsurgical clipping and endovascular treatment. Both microsurgical and endovascular treatment modalities have evolved, in particular with the introduction of innovative endovascular treatment options including flow diversion and intra-saccular flow disruption. These novel therapies allow clinicians to treat more complex and previously untreatable aneurysms. We aim to review the evolution of treatment strategies for intracranial aneurysms over time, and discuss emerging technologies that could further improve treatment safety and functional outcomes for patients with an intracranial aneurysm.